Eficacia del colutorio de manzanilla comparado con el gluconato de clorhexidina al 0.12% en estudiantes con gingivitis inducida por placa de la Carrera de Odontología de la Universidad Nacional de Loja en el periodo octubre - marzo del 2018 - Costa García, Valeria Jazmín (2019)
Gingivitis is the most prevalent gingival disease in society, the correct elimination of dent-bacterial plaque by mechanical control and the use of a chemical agent help in its treatment and prevention. The objective of the study was to compare the efficacy of chamomile mouthwash and 0.12% chlorhexidine gluconate in the reduction of gingival inflammation in patients with plaque-induced gingivitis. It was a comparative, prospective study. Using non-probabilistic sampling for convenience, 30 individuals were selected randomly, assigned to three groups (n = 10) and two groups were assigned chamomile mouthwash or chlorhexidine gluconate (0.12%) and were asked to use 10 ml of rinsing for 60 seconds immediately after tooth brushing, in the morning and at night, for fifteen days; the remaining group was only given hygiene instructions (modified Bass brushing technique). The participants were monitored at 7 and 15 days. The gingival index and the plaque index of Löe and Silness were evaluated. Statistical analysis was performed using the Wilcoxon and Kruskal-Wallis tests to compare the average ranges of the GI and of the initial and final PB in the three study groups and there was evidence of a decrease in GI and PB. It is concluded that chamomile mouthwash is effective in reducing gingival inflammation, but it did not exceed the efficacy of chlorhexidine gluconate. Key words: mouthwash, chamomile, chlorhexidine, gingivitis.